Catalytic Synthesis of π-Conjugated Silole through Si–C (sp3) Bond Activation - Zhang, Qing-Wei; An, Kun; He, Wei (Synlett, 2015)
Conjugated siloles represent an important class of photoluminescence material. Traditional synthesis of siloles often suffered from low functional group compatibility due to the usage of stoichiometric organic lithium or magnesium reagents. In the past years, catalytic Si–C bond activation has emerged as a new strategy for the synthesis of siloles. For the benefit of this fast-developing research area, this article highlights the related pioneering work as well as our recent discovery of a tandem cyclization/Si–C (sp3) activation reaction that enables the rapid synthesis of indole- and benzofuran-conjugated siloles. We also discuss the reaction mechanism in greater detail.
Keywords: silicon; rhodium; tandem reactions; metalation; chemoselectivity